AN EPISTEMOLOGICAL CRITICISM TO LARRY LAUDAN’S SCIENTIFIC METAMETHODOLOGY (Andamios, Revista de Investigación Social, 2007)
This paper is intended to (1) outline the metamethodological proposal by Larry Laudan in his book Beyond Positivism and Relativism (1996), which would provide a foundation for the evaluation of scientific methodologies, that warrants —according to the authorobjectivity in sciences and (2) develop a detailed criticism of two theses from this proposal. I suggest these theses are not justified so that a reformulation or radical change would be needed in order for the objectivity of science to be maintained. However, replacing a metamethodology with another could be misleading, since this eludes the fundamental skeptical problem of the justification of knowledge. I will not conclude the end of philosophy in skepticism; nevertheless, my arguments point towards this very overwhelming direction.
Keywords: Metamethodology; objectivity; relativism; justification of knowledge; skepticism